Sound city : A Guided Tour for Beginner Readers - Hayes, Sarah; Illustrated by Chamberlain, Margaret (London Walker Books Limited, 1998)
This picture book is designed for children learning to read. Each double-spread explores a different sound or group of sounds. Everywhere your look there are signs and labels, speech bubbles, puzzles and funny verses encouraging beginner readers to see that sounds put together make words.
Include Colour Illustrations
Keywords: English language--Phonetics